2010
DOI: 10.1002/aic.12241
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition kinetics and recycle of binary hydrogen‐tetrahydrofuran clathrate hydrate

Abstract: Decomposition kinetics and recycle of hydrogen-tetrahydrofuran (H 2 -THF) clathrate hydrates were investigated with a pressure decay method at temperatures from 265.1 to 273.2 K, at initial pressures from 3.1 to 8.0 MPa, and at stoichiometric THF hydrate concentrations for particle sizes between 250 and 1000 lm. The decomposition was modeled as a two-step process consisting of H 2 diffusion in the hydrate phase and desorption from the hydrate cage. The adsorption process occurred at roughly two to three times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Florusse et al 3 showed that the inclusion of tetrahydrofuran (THF) as a promoter molecule allowed such hydrates to form at ambient conditions. NMR studies 5 and decomposition studies 6 with THF have produced diffusion barriers as low as 3 kJ mol À1 , but this contrasts the rather large barriers found by molecular simulations. Lee et al 4 found that this cost could be tuned by varying the content of THF.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Florusse et al 3 showed that the inclusion of tetrahydrofuran (THF) as a promoter molecule allowed such hydrates to form at ambient conditions. NMR studies 5 and decomposition studies 6 with THF have produced diffusion barriers as low as 3 kJ mol À1 , but this contrasts the rather large barriers found by molecular simulations. Lee et al 4 found that this cost could be tuned by varying the content of THF.…”
mentioning
confidence: 83%
“…In order for the hydrate to be usable as a storage medium, low barriers for gas diffusion are required. NMR studies 5 and decomposition studies 6 with THF have produced diffusion barriers as low as 3 kJ mol À1 , but this contrasts the rather large barriers found by molecular simulations. 7,8 The purpose of this paper is to investigate this discrepancy.…”
mentioning
confidence: 83%
“…The last two stabilizing agents yield relatively high hydrogen storage capacities (1.35 and 1.42 wt%, respectively). Another very well studied and promising promoter for hydrogen clathrate stabilization is tetrahydrofuran (THF), whose addition drastically decreases the formation pressure (Kawamura et al 2011;Prasad et al 2009;Lee et al 2005;Veluswamy and Linga 2013;Nagai et al 2008;Ogata et al 2008;Yoshioka et al 2011;Arca et al 2008). The hydrogen storage capacities in THF-containing binaryclathrate hydrates can be increased up to 4.03 wt% at modest pressures by tuning their composition to allow the hydrogen guests to enter both the larger and the smaller cages, while retaining low-pressure stability.…”
Section: Usage Of Promotersmentioning
confidence: 99%
“…However, contrasting views exist among researchers, with some disputing the influence of THF concentration on H2 storage and failing to replicate comparable storage capacities through tuning [277,286,287]. While tetrahydrofuran (THF) has been extensively studied as a promoter for sII H2 hydrate formation [288][289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304], there is a growing interest in exploring alternative promoters such as dioxolane (DIOX), epoxy(cyclopentane), cyclohexanone, 1,4-dioxane (DXN), tetrahydropyran, and 2,5-dihydrofuran [293,295,300,[305][306][307][308][309][310][311][312][313]. These promoters are being investigated for their potential to enhance thermodynamics, improve hydrate stability, and increase H2 storage capacity.…”
Section: Thermodynamic and Kinetic Promoters For H2 Hydrate Formation...mentioning
confidence: 99%
“…To improve the kinetics of binary H2/THF hydrates, Veluswamy et al [295] utilized a stirred tank reactor (STR) and achieved a maximum H2 storage capacity of 0.19 wt.% within 6 hours at 13.3 MPa and 279.2 K. Other researchers also conducted similar experiments using STR to enhance the kinetics of hydrate formation, as summarized in Table 1.10. Other studies aimed to enhance H2 mass diffusion by exposing high-pressure H2 gas to presynthesized finely crushed THF-hydrate particles [296,299,315]. Although this method demonstrated an increasing trend in H2 storage capacity with rising H2 gas pressure (reaching 1 wt.% at 60 MPa), it is not compatible with continuous cycles as the THF or other promoter hydrate particles revert to the bulk/liquid phase upon melting.…”
Section: Thermodynamic and Kinetic Promoters For H2 Hydrate Formation...mentioning
confidence: 99%